Kaposi's sarcoma in HIV infected women in Germany: more evidence for sexual transmission. A report of 10 cases and review of the literature. Issue 6 (December 1994) - Albrecht, H; Helm, E B; Plettenberg, A; Emminger, C; Heise, W; Schwartländer, B; Stellbrink, H J
Abstract : OBJECTIVE–To assess the natural history of Kaposi's sarcoma (KS) in HIV-positive women living in Germany. METHODS–All physicians reporting the diagnosis of KS in a female patient were contacted and asked for detailed information. DESIGN–Descriptive study of clinical, epidemiological and immunological data of ten women with biopsy-proven KS living in Germany were evaluated. The results are compared with those of other previously published studies of women with KS from Italy, France and the USA. SETTING–Five centres in Germany. RESULTS–Of 765 German women with AIDS, only 10 (1.3%) were reported to suffer from Kaposi's sarcoma (KS) compared with 1771 of 8128 men (21.8%). Mean age in these women was 39.7 years. KS was the first AIDS defining event in nine women and the reason for HIV-testing in three. The mean CD4 count was 215/microliters. Two patients were of African origin, had only recently come to Germany and were most likely to have acquired their HIV-infection in Africa. Three patients were i.v.-drug users (IVDU). Two of these (and most likely all three) had worked as prostitutes. Of five women who had contracted HIV via heterosexual contacts, one worked as a prostitute and the other four were married to or were living together with a bisexual HIV-positive man. All four male partners have also developed KS. The course of the disease seems to be particularly aggressive in female patients with eight of 10 women presenting with or progressing to widely disseminated disease with extensive involvement of internal organs. In this cohort survival was longer in females who acquired their HIV infection heterosexually compared to IVDU and was strongly correlated with higher CD4-counts at diagnosis. CONCLUSIONS–KS seems to run a particularly aggressive course in women. Our data are consistent with a sexually transmittable aetiological agent of KS. Prostitution, an issue yet to be addressed by other authors reporting series of women with KS, was reported in four of our patients. Further studies are needed to clarify the significance of this finding.